2013
DOI: 10.1096/fj.13-235481
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase‐A knockdown in human neuroblastoma cells reveals protection against mitochondrial toxins

Abstract: The study examined how the mitochondrial enzyme monoamine oxidase-A (MAO-A), which produces hydrogen peroxide as a catalytic by-product, influences death and survival mechanisms. Targeted microRNA (miRNA) was used to stably knock down MAO-A mRNA, protein, and catalytic activity by 60-70% in SH-SY5Y human neuroblastoma cells. The effects of MAO-A knockdown (KD) on ATP, oxidative stress, electron transport chain, and survival following exposure to mitochondrial toxins were assessed. In control cells, complex I i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 56 publications
(73 reference statements)
2
18
0
Order By: Relevance
“…Increased DOPAL formation in this setting contributes to rotenone-induced cytotoxicity (Lamensdorf et al, 2000b). Knockdown of MAO-A mitigates rotenone-induced apoptosis (Fitzgerald et al, 2014), consistent with DOPAL, hydrogen peroxide, or both contributing to the toxicity of this pesticide.…”
Section: Aldehyde Detoxification and Catecholamine Autotoxicitymentioning
confidence: 72%
“…Increased DOPAL formation in this setting contributes to rotenone-induced cytotoxicity (Lamensdorf et al, 2000b). Knockdown of MAO-A mitigates rotenone-induced apoptosis (Fitzgerald et al, 2014), consistent with DOPAL, hydrogen peroxide, or both contributing to the toxicity of this pesticide.…”
Section: Aldehyde Detoxification and Catecholamine Autotoxicitymentioning
confidence: 72%
“…Moreover, since MAOs are located at the outer mitochondrial membrane, those compounds are likely to affect proteins in the vicinity, such as Pink1, parkin or the mitofusins, which are involved in mitochondrial quality control [45]. Conversely, it has been shown that MAOA knockdown in neuroblastoma SH-SY5Y cells protects against the detrimental effects of mitochondrial toxins on the respiratory chain [46]. Thus, we postulate that it is the constant degradation of catecholamines generating these toxic molecules which causes all catecholaminergic cells to be a hot spot for the generation of mtDNA deletions.…”
Section: Discussionmentioning
confidence: 99%
“…MAO plays the major role in the development of oxidative stress of the nervous system and heart. When the heart is subjected to chronic neurohumoral and/or peripheral hemodynamic stress, the attendant abundance of circulating/tissue monoamines fuels MAO-derived H 2 O 2 production and has been shown to play in I/R injury [26,32,33]. Recent results demonstrate that MAO is an important determinant of redox balance in human atrial myocardium as well [34].…”
Section: Mitochondrial Sources Of Rosmentioning
confidence: 99%